Corelation between Preoperative Serum CEA, CA19-9, and AFP Levels and Clinicopathologic Factors - Dirican, Abuzer; Unal, Bulent; Isik, Burak; Sumer, Fatih; Kayaalp, Cuneyt; Aslan, Ilhan (Annals of Medical Research, 2021)
None